Profil Kadar Kadmium (Cd) Dalam Urine pada Perokok Aktif - Rita Mustika Sari (Poltekkes Kemenkes Semarang, 2020)
Heavy metal cadmium (Cd) is one of the environmental contaminants harmful and accumulates in the tissues of living creatures. One example of an exposed kamium can ditemukann in smokers. Cadmium contained in cigarette smoke enters through the inhalation then the cadmium is transported in blood and excreted through urine. The levels of cadmium in the body which exceeds the Value of the Threshold can cause damage to the kidneys and liver.The purpose of this study was to determine the picture content of cadmium in the urine of active smokers. Methods this study is no Study of this descriptive type of case report. The sample used comes from the 12 research subjects who are willing to be taken a sample of her urine. The inspection method used is Atomic Absorption Spectrophotometer (AAS).The results of this study are from 12 samples of active smokers in RT 01/I Sendangguwo South results obtained for cadmium content 0,000185 mg/L below Threshold Limit Values.Conclusion this study is an overview of the levels of cadmium in the urine on the whole subject of research under the Threshold Value.